Lower Jaw and Orolabial Analysis in Adult Bangladeshi Buddhist Chakma Females - Mostafa, Asma; Banu, Laila Anjuman; Sultana, Azmeri (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: It is well accepted that a single standard of craniofacial norms is not appropriate for application to diverse racial and ethnic groups, even for different sex and ages in same ethnic group. So it is necessary to develop craniofacial norms for different groups based on above factors. The present study was designed to establish the baseline measurements of the lower jaw and orolabial anthropometrical parameters and indices, and also to evaluate the differences (if any) on age related morphological variations of adult Bangladeshi Buddhist Chakma females. Methods: The study was descriptive, observational and cross-sectional in nature with some analytical components. The study group consisted of a convenient sample of 100 adult Bangladeshi Buddhist Chakma females; categorized into two groups 25 to 35 years (n = 70) and 35 to 45 years (n = 30). Variables were measured using physical and photographic procedures. Indices were calculated from those variables. An independent t test was performed to evaluate if there was any significant difference in measurements between the two age groups setting a p value of <0.05 as statistically significant. Results: All measurements show statistically non significant difference between two age groups except philtrum length (p = 0.02) and upper vermilion height to philtrum length index (p = 0.03). Conclusions: The result of this study can be useful for anatomists and anthropologists to serve as a basic framework for estimating the standard of lower jaw and orolabial dimensions of this population and also to compare the craniofacial dimensions of other ethnic groups of Bangladesh with this ethnic group. Chattagram Maa-O-Shishu Hospital Medical College Journal Volume 12, Issue 3, September 2013: 5-8